Social Interaction in Terms of Practitioners of Extracurricular Sports Activities Among Middle School Students - Thabet Bdiwi Odeh (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Extracurricular sports activities are an important element of the success of school sports, which is one of the educational methods that provide students with many benefits targeting different skills, and the aim of the research was to identify social interaction in terms of practitioners of extracurricular sports activities among middle school students, and to identify any extracurricular sports activities (basketball - volleyball - football) have preference in social interaction, The researcher used the descriptive approach on a sample of students of Al-Mughira Preparatory School bin Division practicing extracurricular activities in basketball, volleyball, and football, and their number is (37) students, using the scale of social interaction, and after collecting data and processing them statistically, the research concluded that there are no differences between the three measurements among practitioners of extracurricular activities in social interaction in basketball and volleyball games. Moreover, football, as a practitioner of extracurricular activities, is characterized by high social interaction.